Assessment of heated herbal products’ tobacco harm reduction potential: pre‐clinical and clinical studies - Marinas-Lacasta, Alvaro-Flavio; Fearon, Ian M.; Stevenson, Matthew; Abusalem, Tasnim; Chapman, Fiona; Trelles Sticken, Edgar; Wieczorek, Roman; Pour, Sarah Jean; Dethloff, Ole; Komini, Ourania; Brown, Mike; Simms, Liam; et al. (Frontiers in Toxicology, 2025)
Data from pre-clinical and clinical studies form part of an integrated assessment of the tobacco harm reduction (THR) potential of novel products that may act as cigarette alternatives for adult smokers. We report data from pre-clinical (emissions chemistry and in vitro toxicology) and clinical (nicotine pharmacokinetics and subjective effects) studies conducted with the iSENZIA™ heated herbal system (HHS; PULZE™ 2.0 device with iSENZIA™ sticks), which utilizes electronic heating of a tea-based substrate to generate an inhalable nicotine-containing aerosol. The aerosols from the iSENZIA™ HHS contained significantly lower levels, by up to 99.8%, of the nine World Health Organization Study Group on Tobacco Product Regulation (WHO TobReg) analytes compared with 1R6F reference cigarette smoke and elicited significantly lower in vitro cytotoxicity, genotoxicity, and mutagenicity responses. The clinical study demonstrated that the iSENZIA™ HHS delivers satisfactory levels of nicotine to users and has lower abuse liability than cigarettes. Overall, our data suggest that iSENZIA™ has the potential to offer substantially reduced toxicant exposure, as well as a reduction in toxicity, compared to cigarettes, while delivering satisfactory levels of nicotine. These findings support the THR potential of the iSENZIA™ HHS as a reduced-risk, acceptable alternative product for adult smokers.